2009
DOI: 10.1182/blood-2009-04-214593
|View full text |Cite
|
Sign up to set email alerts
|

Wild-type FOXP3 is selectively active in CD4+CD25hi regulatory T cells of healthy female carriers of different FOXP3 mutations

Abstract: Forkhead box P3 (FOXP3) is constitutively expressed by CD4 ؉ CD25 hi regulatory T cells (nTregs). IntroductionNaturally occurring CD4 ϩ CD25 hi regulatory T cells (nTregs) play a central role in immune tolerance. nTregs are generated in the thymus, comprise 5% to 10% of peripheral CD4 ϩ T cells, and constitutively express forkhead box P3 (FOXP3), a transcription factor essential for their regulatory activity. 1 Indeed, knockdown of FOXP3 in nTregs reduces suppressive capacity and overexpression of FOXP3 confer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 19 publications
4
43
1
Order By: Relevance
“…For example, Tr1 cells isolated from tolerized human transplant patients do not express Foxp3 but produce high levels of IL-10 (13). In addition, IPEX patients with loss of function mutations in the Foxp3 gene were shown to have suppressive T cell activity through their Tr1 cells, demonstrating that Foxp3 is not required for suppressive Treg cell function in humans (14). The present results are consistent with these human studies, which collectively suggest that the mouse studies showing PSA-specific Foxp3 ϩ iTregs may have limited applicability to human immunology.…”
Section: Cd25supporting
confidence: 83%
See 1 more Smart Citation
“…For example, Tr1 cells isolated from tolerized human transplant patients do not express Foxp3 but produce high levels of IL-10 (13). In addition, IPEX patients with loss of function mutations in the Foxp3 gene were shown to have suppressive T cell activity through their Tr1 cells, demonstrating that Foxp3 is not required for suppressive Treg cell function in humans (14). The present results are consistent with these human studies, which collectively suggest that the mouse studies showing PSA-specific Foxp3 ϩ iTregs may have limited applicability to human immunology.…”
Section: Cd25supporting
confidence: 83%
“…Human Tr1 cells, isolated from tolerant transplant patients, were shown to produce large amounts of IL-10, are typically defined by their high IL-10:IL-4 ratio, and do not express constitutive levels of Foxp3 (13). Because suppressive Tr1 cells can be differentiated from IPEX patients who genetically lack functional Foxp3, it is known that Foxp3 is not required for all suppressive T cell activity in humans (14). Work done by Papadakis et al (15) has demonstrated that mucosal T cells that express the CC chemokine receptor 9 (CCR9) have a suppressive Tr1 cell phenotype.…”
Section: Foxp3 ϩ Peripherally Induced T Regs (Itregs) and Cd4mentioning
confidence: 99%
“…1). Because the mutation was found in two of the three females with AITD, we further explored the females' XCI (see legend) (12,13,14,15,16). Skewing was found in the peripheral blood of the mother and the sister of the patient (both FOXP3 C/K ), but not in the aunt with AITD without a FOXP3 mutation.…”
Section: Resultsmentioning
confidence: 99%
“…FOXP3 is an X-linked gene whose mutated copy will be selectively silenced in the relevant Treg cell population of female carriers (14,16). Thus, no adverse effects ensue from this specific genetic defect, and any risk of autoimmunity in these individuals is therefore most likely due to the respective CTLA4 variant.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, while the functional impairment of FOXP3-mutated Treg cells is undisputed, the identification of circulating cells with figure. specific demethylation of the Treg-cell-Specific-Demethylated-Region (TSDR) (see below), demonstrated that wild type FOXP3 is dispensable for thymic development of Treg cell precursors in humans [44,55]. The lack of functional FOXP3 impairs Treg peripheral maintenance, as demonstrated by the observation that in healthy female carriers of FOXP3 mutations [102] and in transplanted IPEX patients with low peripheral donor chimerism [48] only Treg cells expressing a wild type FOXP3 are detectable in peripheral blood.…”
Section: Thymic Development Of Foxp3-mutated Ttreg Cellsmentioning
confidence: 98%